Monetary and Fiscal Policy Interactions in the Euro Area - Michael Carlberg (Helmut-Schmidt-Universität - Universität der Bundeswehr Hamburg, Fächergruppe Volkswirtschaftslehre, 2004)
This paper studies the interactions between monetary and fiscal policies in the euro area. The focus is on the union central bank, the German government, and the French government. The policy targets are price stability in the union, full employment in Germany, and full employment in France. The policy instruments are union money supply, German government purchases, and French government purchases. As a rule, the spillovers of fiscal policy are negative. The policy decisions are taken sequentially or simultaneously. This paper carefully discusses the case for central bank independence and fiscal cooperation between Germany and France.
urn:nbn:de:gbv:705-opus-1911
Keywords: E12; F33; E63; F42; F41; 330; European Monetary Union; International Policy Coordination; Monetary Policy; Fiscal Policy; Finanzpolitik; Geldpolitik; Europäische Wirtschafts- und Währungsunion; Internationale wirtschaftspolitische Koordination; Spillover-Effekt; Theorie